Effect of incorporation of cardamon powder on physiochemical, sensory attributes, and shelf life of a cow and buffalo milk paneer - Kandel, Kamana; Thagunna, Bishal; Dhakal, Yashoda; Rimal, Anju (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2023)
Paneer is a nutritious, delectable acid-heat-coagulated indigenous dairy product, but it has a short shelf life due to its high moisture content. However, herbs are known for their qualities as antioxidants, preservatives, and flavor enhancers. Therefore, the current study examined the quality parameters such as (titratable acidity, lactose, moisture content, ash content, fat content, protein content, phenolic content, and sensory parameters) of herbal paneer produced by incorporating cardamom powder percentages in four different samples 0.15% with cow milk, 0.20% with cow milk, 0.15% with buffalo milk and 0.20% with buffalo milk and coded as (A, B, C, and D). The findings showed that the herbal paneer was superior in terms of organoleptic but had little to no impact on the paneer's proximate and physiochemical parameters. The herbal paneer samples slightly higher total phenolic content of buffalo milk paneer compared to the cow milk paneer. The 0.20% of cardamom with buffalo milk sample was effective overall. As a result, the study suggests that cardamom could be used to develop a novel functional dairy product with enhanced antioxidant properties and longer shelf life.